Contextual Similarity Between Successive Targets Modulates Inhibition of Return in the Target-Target Paradigm - Chao, Hsuan-Fu; Kuo, Chun-Yu; Chen, Makayla S.; Hsiao, Fei-Shan (Frontiers in Psychology, 2020)
Inhibition of return (IOR) refers to slower responses to a target presented at a previously cued versus uncued location. The present study investigated the role of memory retrieval in IOR by manipulating the contextual similarity between two successive targets in the target-target IOR paradigm. Successive targets were presented in either the same color (same-context condition) or different colors (different-context condition). Results of two experiments showed that IOR was greater in the same-context than the different-context condition. In addition, Experiment 2 showed that this context effect occurs with long response times, suggesting that memory retrieval, which requires time to manifest, plays an important role in IOR.